All Days 2011
DOI: 10.2118/139766-ms
|View full text |Cite
|
Sign up to set email alerts
|

Casing Burst Stresses in Particulate-Filled Annuli: Where's the Cement?

Abstract: For burst design, engineers routinely assume the casing annular space is filled by a fluid equivalent. This assumption ignores mechanical resistance provided by solid cement. Some studies addressed this shortcoming by modeling the cement sheath as a solid with elastic failure criteria. Prior work used cement elastic modulus and Poisson ratio to classify cement as 'ductile' (soft) or 'brittle' (hard).In the current study, numerical results from finite element analysis (FEA) indicate that casing burst resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The CO 2 injection zone of WH 802 is from 5357 ft to 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6600 ft. Figure 6 shows the structure of WH-802. The packer depth is 5257 ft and the inject tubing depth is 5307 ft. Table 2 presents properties of cement sheath and formation (Kalil and McSpadden, 2012). The mechanical properties of cement sheath and formation are unclear.…”
Section: Analysis With Field Datamentioning
confidence: 99%
“…The CO 2 injection zone of WH 802 is from 5357 ft to 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6600 ft. Figure 6 shows the structure of WH-802. The packer depth is 5257 ft and the inject tubing depth is 5307 ft. Table 2 presents properties of cement sheath and formation (Kalil and McSpadden, 2012). The mechanical properties of cement sheath and formation are unclear.…”
Section: Analysis With Field Datamentioning
confidence: 99%
“…In recent years, severe casing damage in deep salt strata has been carefully followed and comprehensively studied by many scholars. Salt rock creep leads to open wellbore shrinkage and casing collapse [5][6][7][8], the well condition and casing performance are getting worse under high pressure and high temperature [1,9], and another cause of casing damage is cement sheath failures [4,10,11]. However, to simplify the calculation, prior work on casing damage in deep salt formation only considered the impact of a single factor, ignoring interaction between salt rock creep, defective cement, and HPHT, which has great deviations from actual situation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with more and more field data demonstrates that well casings designed by API bulletin 5C3 occur failure under salt creep conditions though their designed safety factors are greater than 1. 8,9 Some authors 3,8–13 begin to turn their sights on the cement and formation, which closely connected with the safety of well casings, in summary, their studies indicated that cement missing or deboning changes the stress distribution of the casing, resulting in well casings bearing nonuniform loading; the flowing of salt formation changes the existing local stress field and displacement field, resulting in the time-dependent nonuniform loading on well casings. Previous studies given us enlightenment that formation, cement and casing are an inextricably linked system when it comes to casing failure.…”
Section: Introductionmentioning
confidence: 99%